Capital Structure Policy and Firm Value of Micro, Small, and Medium Enterprises: a Case Study of Culinary Sector - Triraharjo (19015128), Adiguna
Gross Domestic Product growth is usually related with the economic standing of a country. In the past several years, Indonesia GDP growth has been declining. However the economic bounce back can been seen after having fluctuative growth in 2016, indicates that more of its populations are having higher purchasing power. Following previous researches that state GDP growth is closely related to the growth of small and medium enterprises, which in Indonesia itself, the contribution is Rp 7.005.950 billion or about 62.57% of total GDP. This research aims to find the corellation between the capital structure and affects to the valuation of the MSMEs. This thesis examine the financial performance of micro, small, and medium enterprises using Discounted Cash Flow followed by finding the correlation between the capital structure using its debt ratio with the value of the firm to see if there is any correlation between the MSMEs financial performance and its capital structure using spearman non-parametric correlation test. The data needed to analyze in this research are based on the primary data of financial records gathered from thirty micro, small, and medium enterprises. It was found that the debt ratio has positive impact to the value of the firm. This indicate that investor funding will not preferable than taking loan from the bank. This way of obtaining capital will also result in higher valuation of the MSMEs, making the firms more valuable in investor perspective. So, this study recommends micro, small, and medium enterprises to use more debt when funding is necessary to grow the business and reach higher valuation.